Plan de marketing-proyecto primates del Sur. - Narvaez Ramon, Diana Carolina; Sarmas Pambi, Nathaly Yulissa (My University, 2021)
This document consists of research on nature-scientific tourism in the Canton Las Lajas parish La Libertad, giving value to it and promote it through a tourism marketing plan in order to generate local development by turning the sector as a secondary source of income for the community, another important point in this context is that the place has natural resources for those tourists who love nature and for those people who conduct research on the flora and fauna in the area. To carry out the marketing plan, marketing mix strategies will be used to attract the attention of potential future clients. The strategies are: Product: Offer a variety of tourist activities to satisfy the needs and desires of tourists. Price: Set an affordable price to maintain customer loyalty. Place: To make tourist sites known effectively and quickly. Promotion: Carry out tourism promotions that are the main component in order to attract more customers, promoting existing tourist attractions. The components of contribution for the investigation were the bibliographic sources, the surveys directed to tourists belonging to the different cantons and the use of the MINTUR's hierarchical cards with the visit to the site for the update of the information in order to obtain real data. Within what corresponds to the methodology, the descriptive type of research was used considering that through the results of the surveys carried out to the population it is based in a quantitative and qualitative way with the purpose of knowing the viability and acceptance of the nature-scientific tourism to generate a tourist development. The results show the acceptance of this type of tourism for the parish of La Libertad, since it is considered important to generate income, benefits for the community and also allows to promote local enterprises in such a way that the Governance is the one who should provide initiatives and support as the competent authority for tourism companies to invest in the sector generating employment for local residents. The purpose is to generate a different type of tourism and to offer tours according to the resources that the place has, such as a Full Day, it is possible to know the tourist sites, provide new experiences to tourists and perform activities related to nature compared to traditional tourism of sun and beach. It is important that the authorities of the parish of La Libertad have an official website so that the tourist has all the necessary information when visiting the place, as well as information about tourist attractions, food and beverage establishments, lodging, etc. In such a way that when you are in the place you have access to all the services and make your stay a unique experience. On the other hand, there is the possibility that people who travel for scientific research reasons, come to the place, since having endemic species are an important source of research and support for future projects.
El presente documento consta de investigación sobre el turismo naturaleza-científico en el Cantón Las Lajas parroquia la Libertad, dando valor al mismo e impulsarlo a través de un plan de marketing turístico con la finalidad de generar un desarrollo local convirtiendo al sector como fuente secundaria de ingreso para la comunidad, otro punto importante en este contexto es que el lugar posee recursos naturales para aquellos turistas amantes de la naturaleza y para aquellas personas que realizan investigaciones de la flora y fauna existente en la zona. Para llevar a cabo el plan de marketing se utilizarán las estrategias de marketing mix, lo que permitirá llamar la atención de futuros clientes potenciales.Producto: Ofrecer variedad de actividades turísticas para satisfacer las necesidades y deseos de los turistas. Precio: Fijar un precio accesible al cliente para así mantener su fidelidad. Plaza: Dar a conocer de forma efectiva y rápida los lugares turísticos. Promoción: Realizar promociones turísticas que sean el componente principal con el fin de captar más clientes, fomentando los atractivos turísticos ya existentes. Los componentes de aporte para la investigación fueron las fuentes bibliográficas, las encuestas dirigidas a turistas pertenecientes a los diferentes cantones y la utilización de las fichas de jerarquización del MINTUR con la visita al sitio para la actualización de la información con el fin de obtener datos reales. Dentro de lo que corresponde a la metodología, se empleó el tipo de investigación descriptiva considerando que a través de los resultados de las encuestas realizadas a la población se base de manera cuantitativa y cualitativa con el propósito de conocer la viabilidad y aceptación del turismo de naturaleza-científico para generar un desarrollo turístico. Mediante los resultados da como aceptación este tipo de turismo para la parroquia La Libertad, ya que es considerado importante para generar ingresos, beneficios para la comunidad y además permite impulsar emprendimientos locales de tal forma que la Gobernanza es quien debe brindar iniciativas y apoyo como autoridad competente para que las empresas turísticas inviertan en el sector generando empleo a personas residentes del lugar. El propósito es poder generar un tipo de turismo diferente y al ofrecer tours de acuerdo a los recursos que posee el lugar, como por ejemplo un Full Day es posible conocer los lugares turísticos, brindar nuevas experiencias al turista y realizar actividades vinculado con la naturaleza a comparación del turismo tradicional de sol y playa. Es importante que las autoridades de la parroquia La Libertad tenga página oficial para que el turista posea toda la información necesaria al momento de visitar el lugar, al igual que información de los atractivos turísticos, establecimientos de alimentos y bebidas, hospedaje, etc. De tal forma que al encontrarse en el lugar tenga acceso a todos los servicios y hacer su estadía una experiencia única. Por otro parte existe la posibilidad de que personas que viajan por motivos de investigación científica, lleguen al lugar, ya que al contar con especies endémicas son una fuente importante de investigación y apoyo para futuros proyectos.
Keywords: TURISMO NATURALEZA; ACTIVIDADES TURÍSTICAS; MARKETING MIX; SECTOR TURÍSTICO